2019
DOI: 10.1111/ctr.13694
|View full text |Cite
|
Sign up to set email alerts
|

Discharge frailty following lung transplantation

Abstract: Introduction: Frailty at listing for lung transplant has been associated with waitlist and post-transplant mortality. Frailty trajectories following transplant, however, have been less well characterized, including whether recipient frailty improves. The objective of this study was to identify prevalence and risk factors for frailty at discharge and to evaluate changes in frail recipients enrolled in an outpatient physical therapy program. Methods:This was a single-center prospective cohort study of lung trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…The SPPB increased over five points in patients who were frail pre‐transplant with most of the improvement occurring in the first six months. Courtwright and colleagues reported that of 111 LTx recipients (all non‐frail pre‐transplant), 54% were frail at the time of hospital discharge following transplantation 13 . Of 35 patients who were frail at discharge and attended outpatient physiotherapy (average of 75 days), the SPPB score increased a median of six points and 86% were no longer considered frail upon program completion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SPPB increased over five points in patients who were frail pre‐transplant with most of the improvement occurring in the first six months. Courtwright and colleagues reported that of 111 LTx recipients (all non‐frail pre‐transplant), 54% were frail at the time of hospital discharge following transplantation 13 . Of 35 patients who were frail at discharge and attended outpatient physiotherapy (average of 75 days), the SPPB score increased a median of six points and 86% were no longer considered frail upon program completion.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of data regarding the association between pre‐transplant frailty/pre‐frailty and early post‐transplant hospital and exercise capacity outcomes in the first three months. Physical frailty may be responsive to rehabilitation, 11 and improvements in SPPB have been demonstrated following LTx 12,13 . Frailty trajectories in the pre‐transplant period are not well characterized, and it is not known whether frailty/pre‐frailty is remediable in LTx candidates with end‐stage lung disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with lower SPPB scores (indicative of more frailty) had considerably higher risk of readmission as compared to those with a higher score (indicative of less frailty). Later, Courtwright et al 11 proceeded to investigate changes in SPPB scores in frail recipients enrolled in an outpatient rehabilitation program with findings that 86% of patients were no longer frail over a median of 6 weeks. 11 Finally, a finding to be highlighted is that patients who underwent transplant between 2004 and 2010 were at a higher risk for readmissions than those after 2010, 6 which may account for advances in surgical and immunosuppression techniques of the present decade.…”
Section: Risk Factors For Readmissions After Lung Transplantationmentioning
confidence: 99%
“…An earlier study suggested increased risk of death and delisting in lung transplant candidates living with frailty (11). We also know that frailty is common at discharge after lung transplantation (12). Somewhat surprisingly, frailty does not seem to correlate with length of hospital stay nor with 1-year mortality (13).…”
Section: Introductionmentioning
confidence: 96%